HEALTHY BEHAVIOR MANAGEMENT IN THE IMPLEMENTATION OF THE NEW NORMAL ERA IN THE COVID-19 PANDEMIC - Musdalifah, Musdalifah; Pattola, Pattola; Nildawati, Nildawati (Homes Journal: Hospital Management Studies Journal, 2022)
Health behavior and Covid 19 have a close relationship with social interaction in the era of new normal implementation in the midst of this Covid-19 pandemic. The purpose of this study is to find out the health behavior of the new normal during the Covid-19 pandemic in the community. This research is a type of quantitative research with a descriptive approach. Sampling was conducted by Non Probability Sampling technique using accidental sampling method of 120 respondents and conducted by using online questionnaire (google form), the questionnaire was shared in the form of links to social media that can be accessed by the public. The results showed that the health behavior of the community in the implementation of the new normal era during this pandemic showed 32.5% of respondents are well category, 57.5% of respondents are quite good category, and 10% of respondents are less good category. From this research data can be concluded that health behavior in the implementation of the new normal era in the midst of the Covid-19 pandemic the majority of respondents are quite good category. It is influenced by age, education, employment, and gender factors.